The prevention and treatment of retinal complications in diabetes (02.12.2016) - Schorr, Susanne; Hammes, Hans-Peter (Deutsches Ärzteblatt, 2016)
Diabetic retinopathy and maculopathy are microvascular complications of diabetes that can permanently damage vision, potentially leading to blindness. In Germany, the age- and sex-standardized prevalence of diabetes among persons covered by statutory...